Brief communication: 5‐HTTLPR genetic diversity and mode of subsistence in Native Americans. Issue 3 (17th May 2013) - Bisso‐Machado, Rafael; Ramallo, Virginia; Tarazona‐Santos, Eduardo; Salzano, Francisco M.; Bortolini, Maria Cátira; Hünemeier, Tábita
ABSTRACT The relationship between the "individualism‐collectivism" and the serotonin transporter functional polymorphism (5‐HTTLPR), suggested in the previous reports, was tested in Native South Amerindian populations. A total of 170 individuals from 21 populations were genotyped for the 5‐HTTLPR alleles. For comparative purposes, these populations were classified as individualistic (recent history of hunter–gathering) or collectivistic (agriculturalists). These two groups showed an almost identical S allele frequency (75 and 76%, respectively). The analysis of molecular variance showed no structural differences between them. Behavioral typologies like those suggested by JY Chiao and KD Blizinsky (Proc R Soc B 277 (2010) 529–537) are always a simplification of complex phenomena and should be regarded with caution. In addition, classification of a whole nation in the individualist/collectivist dichotomy is controversial. The focus on modes of subsistence in preindustrial societies, as was tested here, may be a good alternative although the postulated association between the 5‐HTTLPR S allele and the collectivist societies was not confirmed. Am J Phys Anthropol 151:492–494, 2013.© 2013 Wiley Periodicals, Inc.